Antifungal, anti-inflammatory and antioxidant activity of bi-herbal mixtures with medicinal plants from Argentinean highlands. (10th May 2020) - Moreno, María Alejandra; Zampini, Iris Catiana; Isla, María Inés
Abstract: Ethnopharmacological relevance: Argentinean medicinal plants such as Larrea divaricata Cav., Larrea cuneifolia Cav., Larrea nitida Cav., Zuccagnia punctata Cav. and Tetraglochin andina Ciald. are used alone and in combination in traditional medicine by inhabitants from northwestern Argentina to solve mycosis, vaginal infections, gastrointestinal, respiratory, and inflammatory processes. Aim of the study : To assess the effect of interactions between hydroalcoholic extracts of these five species of medicinal plants against yeast strains isolated from vaginal infections, select the most active mixtures and evaluate anti-inflammatory and antioxidant activities. Material and methods: Synergy between the plant extracts was studied by using a broth microdilution assay by means of the checkerboard method against Saccharomyces cerevisiae, Candida albicans, and non albicans strains. The inhibitory effect on lipoxygenase and the antioxidant capacity in cell-free and cell systems were studied. The chemical profile was evaluated by qualitative and quantitative screening, whereas chemical markers were quantified by HPLC-DAD. Results: A synergistic antifungal effect was observed in some binary combinations. Z. punctata/L. divaricata, Z. punctata / L. cuneifolia, and Z. punctata/L. nitida were the most active mixtures. Nordihydroguaiaretic acid and 2′, 4′-dihydroxychalcone, two antifungal compounds, present in these extracts, were identified and quantified by HPLC-DAD. Both single extracts and bi-herbal mixtures showed antioxidant activity (in cellular and in cell-free systems) and were active on pro-inflammatory enzymes (LOX). Conclusions: Our results indicated that the most active combinations of these species extracts could be useful in the treatment of vaginal infectious diseases caused by Saccharomyces cerevisiae and Candida spp. strains and in associated oxidative and inflammatory processes, supporting its traditional use. In addition, the results highlighted the phyto-therapeutic potential of total phytochemical compounds present in these medicinal plants. Graphical abstract: Image 1 Highlights: Plant species of Argentine highlands are used as antifungal in popular medicine. Extracts were effective against yeast strains isolated from vaginal infections. Bi-herbal mixtures showed synergistic or additive antifungal effect. Extracts and bi-herbal mixtures showed antioxidant and anti-inflammatory activity. Extracts and bi-herbal mixtures were standardized by chemical composition.